In vitro evaluation of the influence of air abrasion on detection of occlusal caries lesions in primary teeth - Rodrigues, Jonas de Almeida [UNESP]; de Vita, Thais Maria [UNESP]; Loiola Cordeiro, Rita de Cassia [UNESP] (Amer Acad Pediatric Dentistry, 2008)
Purpose: The purpose of this study was to assess the influence of cleaning pits and fissures with on aluminum oxide air abrasion system on the detection of occlusal caries in primary teeth using laser fluorescence (LF) and visual examination. Methods. The sample comprised 65 pit and fissure sites on extracted primary teeth suspected to be carious. The sites were submitted to 2 visual examinations (examiner JAR) and 2 LF readings (examiner TMV). Next, the occlusal surfaces were air-abraded and re-examined thereafter using both methods. The teeth were sectioned, and the histological analysis of the sites with a stereoscopic magnifying lens at X32 magnification was used as the gold standard Results. Cohen's kappa statistic for LF and visual examination were, respectively, 0.282/0.884 before and 0.896/0.905 after air abrasion. LF showed a sensitivity of 0.28 increasing to 0.49 and 0 specificity of 0.50 increasing to 0.92. Visual examination showed sensitivity of 0.78 and specificity of 0.73. Both increased after air abrasion. Conclusion: The findings suggest that cleaning pits and fissures with aluminum oxide air abrasion increased the accuracy of LF and visual examination for detection of occlusal caries in primary teeth.
Keywords: occlusal caries; caries detection; laser fluorescence; air abrasion; primary teeth